Exploration of Weak Acid Solvent Usage in the Separation of Aluminum (Al) from Multilayer Plastic Waste - Selpiana, Selpiana; Haryani, Nina; Putri, Rizka Wulandari (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2025)
Multilayer plastic waste is difficult to biodegrade, causing environmental problems. An alternative to processing multilayer plastic waste is to separate aluminum from the polymer using a delamination process with acid solvents. In this study, a combination of chemical (acid solvents), thermal (90oC), and mechanical (stirring at 300 rpm) methods was employed to evaluate the efficiency of delamination of multilayer plastic packaging. Several weak acid solvents, including acetic acid, citric acid, and formic acid, were tested at a concentration of 30% and a reaction time of 10 minutes. The method involved immersing cut multilayer plastic samples into acid solutions under controlled conditions, followed by filtration and drying to recover the aluminum layer. The best result was obtained using 30% formic acid, which successfully separated and recovered 0.940 g or 87% of aluminum from a 1.08 g multilayer sample. This process demonstrates an effective, relatively low-cost approach to enhance the recyclability of multilayer plastic waste, contributing to a more sustainable plastic waste management strategy.